Lighting of Museums and Art Galleries. (October 2020) - Piana, E.A.; Merli, F
Abstract: A museum is a place where people can explore and learn the past, the present and the future of culture and science. Amongst the other technical systems, the lighting equipment must satisfy a number of requirements. For each project, lighting designers must face challenges in order to encompass the given specifications in a single lighting concept: protection of the artefacts, economic convenience, architectural constraints and, last but not least, the creative ambitions of the artist. This paper analyses the lighting environment of a real art gallery with the aim to identify a satisfactory solution in terms of enjoyment, artefact preservation and energy consumption. By means of a simulation software, suitable general and spot lighting devices are chosen to fulfil the requirements whilst avoiding damages to the artefacts, and lighting parameters are obtained to evaluate the proposed solution. The work shows that advanced LED technologies can be effectively used to modify a museum lighting environment and turn it into the classical gallery archetype.